The Effect of Position Promotion, Training, Leadership Style on Employee Career Development in One of the Start Up Companies - Anita Lestari; Syamsu Rijal; Yuditia Prameswari; Teddy Tjahyanto; Dana Budiman (West Science Business and Management, 2023)
This research study explores the effect of promotion practices, training initiatives, and leadership style on employee career development in a start-up company. The study employs a mixed-methods research design, including quantitative surveys and qualitative interviews, to gather comprehensive data. The findings from the quantitative analysis indicate a positive correlation between promotion opportunities and employee career advancement, as well as a positive relationship between the effectiveness of training programs and perceived skill development. The qualitative analysis reveals the importance of supportive and empowering leadership behaviors and the impact of specific training initiatives on employee career growth. The integration of quantitative and qualitative findings provides a holistic understanding of the factors influencing employee career development in start-up companies. The implications of the study contribute to theoretical knowledge and offer practical recommendations for start-up companies to optimize promotion practices, training initiatives, and leadership styles to support employee career development.